2017
DOI: 10.1128/aem.01128-17
|View full text |Cite
|
Sign up to set email alerts
|

Med15B Regulates Acid Stress Response and Tolerance in Candida glabrata by Altering Membrane Lipid Composition

Abstract: Candida glabrata is a promising producer of organic acids. To elucidate the physiological function of the Mediator tail subunit Med15B in the response to low-pH stress, we constructed a deletion strain, C. glabrata med15BΔ, and an overexpression strain, C. glabrata HTUΔ/CgMED15B. Deletion of MED15B caused biomass production, glucose consumption rate, and cell viability to decrease by 28.3%, 31.7%, and 26.5%, respectively, compared with those of the parent (HTUΔ) strain at pH 2.0. Expression of lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 60 publications
1
46
0
Order By: Relevance
“…Third, sterols, abundant apolar membrane lipids, can increase membrane thickness and impermeability by reducing the flexibility of the surrounding acyl chains (59). In our previous study, we also showed that increasing the ergosterol content by overexpression of Cg-MED15 may enhance membrane fluidity, thereby promoting the resistance to low pH (60). Importantly, to manipulate the ratio of these membrane lipids, compensatory mechanisms exist in yeast.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Third, sterols, abundant apolar membrane lipids, can increase membrane thickness and impermeability by reducing the flexibility of the surrounding acyl chains (59). In our previous study, we also showed that increasing the ergosterol content by overexpression of Cg-MED15 may enhance membrane fluidity, thereby promoting the resistance to low pH (60). Importantly, to manipulate the ratio of these membrane lipids, compensatory mechanisms exist in yeast.…”
Section: Discussionmentioning
confidence: 86%
“…The marker genes were amplified from the C. glabrata strain ATCC 2001 genome and fused between the upstream and downstream regions of the CgRDS2 or CgHOG1 gene open reading frame by fusion PCR. PCR products were transformed in the Candida glabrata strain CgHTUΔ as described previously (60), and the deletion strains were confirmed by genomic PCR and DNA sequencing. Overexpression strains were constructed using the pY26 plasmid carrying the target genes.…”
Section: Methodsmentioning
confidence: 99%
“…This as other H + /V + -ATPases have been shown to be inhibited when membrane fluidity is reduced. 49,[51][52][53][54] Separately, we and others have found that SNARE function can be altered by membrane fluidity. 32,33,55 Together, these notions and the data presented add another facet to pleiotropic effects of this metal to include membrane fusion.…”
Section: Copper Inhibits V-atpase Activitymentioning
confidence: 84%
“…PssA overexpression increases PE zwitterionic phospholipid content (Tan et al, ). Other methods of regulating membrane lipids include transcription factors such as Rds2 and Crz1 (Wu et al, ; Yan et al, ) and mediators such as Med15B (Qi, Liu, Yu, Chen, & Liu, ), which are applied to manipulate gene transcription level. These approaches do not directly engineer cell membranes and are not strongly dependent on phospholipid pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of regulating membrane lipids include transcription factors such as Rds2 and Crz1 (Wu et al, 2019;Yan et al, 2016) and mediators such as Med15B (Qi, Liu, Yu, Chen, & Liu, 2017), which are applied to manipulate gene transcription level.…”
Section: Assembly Of Phospholipid Components Enhances Membrane Intementioning
confidence: 99%